Identification of Mycobacterium tuberculosis Infection in Infants and Children With Partial Discrimination Between Active Disease and Asymptomatic Infection - Dreesman, Alexandra; Dirix, Violette; Smits, Kaat; Corbière, Véronique; Van Praet, Anne; Debulpaep, Sara; De Schutter, Iris; Felderhof, Mariet-Karlijn; Malfroot, Anne; Singh, Mahavir; Locht, Camille; Mouchet, Françoise; et al. (Frontiers in Pediatrics, 2019)
Background: Improved diagnostic tests are needed for the early identification of Mycobacterium tuberculosis-infected young children exposed to an active TB (aTB) index case. We aimed to compare the diagnostic accuracy of new blood-based tests to that of the tuberculin skin test (TST) for the identification of all infected children and for a potential differentiation between aTB and latent TB infection (LTBI). Methods: 144 children exposed to a patient with aTB were included, and those who met all inclusion criteria (130/144) were classified in three groups based on results from classical investigations: non-infected (NI: n=69, 53%, median age 10 months), LTBI (n=28, 22%, median age 96 months), aTB disease (n=33, 25%, median age 24 months). The first whole blood assay consisted of a 7-days in vitro stimulation of blood with four different mycobacterial antigens (40µl/condition), followed by flow cytometric measurement of the proportions of blast cells appearing among lymphocytes as a result of their specific activation. Thresholds of positivity were determined by ROC curve analysis (results of NI children versus children with LTBI/aTB) in order to identify infected children in a first stage. Other cut-offs were determined to discriminate subgroups of infected children in a second step (results from children with aTB/LTBI). Analysis of blood monocytes and dendritic cell subsets was performed on 100 µl of blood for 25 of these children as a second test in a pilot study. Results: Combining the results of the blast-induced CD3+ T lymphocytes by Heparin-Binding Haemagglutinin and by Culture Filtrate Protein-10 identified all but one infected children (sensitivity 98.2% and specificity 86.9%compared to 93.4% and 100% for the TST). Further identification among infected children of those with aTB was best achieved by the results of blast-induced CD8+ T lymphocytes by purified protein derivative (sensitivity for localized aTB: 61.9%, specificity 96.3%), whereas the proportions of blood type 2 myeloid dendritic cells (mDC) were a hallmark of LTBI. Conclusions: New blood-based tests requiring a very small volume allow the accurate identification of M. tuberculosis-infected young children among exposed children and are promising to guide the clinical classification of children with aTB or LTBI.